Draft genome sequencing of Tilletia caries inciting common bunt of wheat provides pathogenicity-related genes - Gurjar, Malkhan Singh; Kumar, Tej Pratap Jitendra; Shakouka, Mohamad Ayham; Saharan, Mahender Singh; Rawat, Laxmi; Aggarwal, Rashmi (Frontiers in Microbiology, 2023)
Common bunt of wheat caused by Tilletia caries is an important disease worldwide. T. caries TC1_MSG genome was sequenced using the Illumina HiSeq 2500 and Nanopore ONT platforms. The Nano pore library was prepared using the ligation sequencing kit SQK-LSK110 to generate ~ 24 GB for sequencing. The assembly size of 38.18 Mb was generated with a GC content of 56.10 %. The whole genome shotgun project was deposited at DDBJ/ENA/GenBank under the accession JALUTQ000000000. 46 contigs were obtained with N50 of 1,798,756 bp. 10,698 genes were predicted in the assembled genome. Out of 10,698 genes, 10,255 genes were predicted significantly in the genome. The repeat sequences made up about 1.57 % of the genome. Molecular function, cellular components, and biological processes for predicted genes were mapped into the genome. In addition, repeat elements in the genome were assessed. 0.89 % of retroelements were observed, followed by long terminal repeat elements (0.86%) in the genome. Simple sequence repeat analysis, 8,582 SSRs were found in the genome assembly. Trinucleotide SSR type (3703) was the most abundant. Few putative secretory signal peptides and pathogenicity-related genes were predicted. The genomic information of T. caries will be valuable in understanding the pathogenesis mechanism as well as developing new methods for the management of common bunt disease of wheat.